Analisis Metafora dalam Lirik Lagu Satu Tuju dan Kau Rumahku Karya Raissa Anggiani - Azzahra, Aulia; Faarisah, Shabrina; Nurjanah, Neneng (UIR PRESS, 2023)
The purpose of this study is to describe the metaphors found in the lyrics of the song